Neuropsychiatric manifestations of systemic lupus erythematosus: The value of anticardiolipin, antigangliosides and antigalactocerebrosides antibodies - Costallat, L. T.L. (1990)
In an attempt to find a serological marker for neuropsychiatric manifestations (NPM) of SLE, sera from 66 patients (classified in three groups, according to their NPM - defined, probable and without NPM) were analysed by ELISA for IgG and IgM anticardiolipin, antigangliosides and antigalactocerebrosides antibodies. A strong correlation was found between IgM antigangliosides and antigalactocerebrosides antibodies and NPM, but not with IgG class. IgM and IgG antibodies anticardiolipin were not correlated with NPM in this study. Both IgM antigangliosides and antigalactocerebrosides antibodies disappeared in seven patients with definite but clinically inactive NPM. The analysis of these autoantibodies showed an important role predictive for NPM in SLE; the negative test decreases the chance of the NPM. © 1990 Springer-Verlag.